Uber in the Portuguese gig economy: a laboratory for platform capitalism. (1st January 2020) - Leonardi, Emanuele; Pirina, Giorgio
Abstract : The paper frames the emergence of the Portuguese gig economy within the broader process of platformisation of work in Europe as set in motion by the neoliberal turn at a global scale. Against this background the case of Portugal in general and that of Lisbon in particular are analysed to show both their consistency with the general trends of the European Union's economic dynamics and their irreducible peculiarities. These latter particularities, and especially the so-called 'Uber Law', are discussed in connection with the hypothesis of a specifically Portuguese variety of the gig economy.